The Effectiveness of a Genre-Based Approach to Enhance University-Level Nursing Students' Speaking Performance - Hendra Putra; Rudi Hartono; Januarius Mujiyanto; Yuliati Yuliati (Ta'dib)
: Students can comprehend the nursing process and disease cases thanks to the nursing study program's English syllabus.  Thus, the purpose of this study is to determine how well the Genre-Based Approach (GBA) improves university-level nursing students' speaking abilities. The study employs a quasi-experimental research design and quantitative methods.  The purpose of this study was to determine whether or not GBA can improve university-level speaking abilities among nursing students.  A complete sampling technique is used to choose the sample, which consists of 71 students in total.  The GBA is used to teach English in the experimental group.  In contrast, the control group receives English instruction using a traditional method. the information gathered from the pre-test and post-test. Both descriptive and inferential analysis are performed on the data using the SPPS 22 version application. In hypothesis testing, 0.05 is a common significance level. Since 0.530 is more than 0.05, the null hypothesis—which typically states that there is no difference between the groups—cannot be disproved. It shows that H0 is accepted while Ha is denied. As a result, one could argue that there aren't any notable differences between the groups.